2019
DOI: 10.2147/ott.s194986
|View full text |Cite
|
Sign up to set email alerts
|

<p>Histone deacetylase 6 is overexpressed and promotes tumor growth of colon cancer through regulation of the MAPK/ERK signal pathway</p>

Abstract: Purpose: To investigate the expression of histone deacetylase 6 (HDAC6) in colon cancer and its role in colon cancer cell growth and migration. Materials and methods: We detected the expression of HDAC6 in a colon cancer tissue chip using immunochemical staining, and analyzed the difference in HDAC6 expression between cancer and adjacent noncancerous tissues. Then, we explored the relationship between HDAC6 expression and patients’ clinicopathological characteristics and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 39 publications
(33 reference statements)
0
33
0
Order By: Relevance
“…Additionally, our findings also revealed that E2F7 promoted MAPK stability to enhance cell proliferation, invasion, and migration in colon cancer. Similarly, a prior study elucidated the association of the MAPK signaling pathway with colon cancer growth in vivo ( 27 ). Notably, MAPK has been found to promote colon cancer tumor stem cell activity ( 15 ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, our findings also revealed that E2F7 promoted MAPK stability to enhance cell proliferation, invasion, and migration in colon cancer. Similarly, a prior study elucidated the association of the MAPK signaling pathway with colon cancer growth in vivo ( 27 ). Notably, MAPK has been found to promote colon cancer tumor stem cell activity ( 15 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, donepezil failed to increase the p-AKT/AKT ratio in the hippocampus. Previous studies have also indicated that p-AKT is decreased upon the knockdown of HDAC6 [ 28 ], which implies that AKT is associated with the regulation of HDAC6. However, further investigation is needed to confirm the relationship between HDAC6 nuclear translocation and p-AKT.…”
Section: Discussionmentioning
confidence: 92%
“…HDAC6 overexpression promotes colorectal tumor growth and selective inhibition synergistically induces CRC cell death (39). Recently we described a selective hydroxamate-based small-molecule HDAC6 inhibitor (C1A), with good pharmacokinetics and ability to modulate autophagy in vitro and in vivo in different cancer subtypes including CRC cells (12).…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of HDAC6 was found to be associated with larger tumor sizes in CRC indicating its key role in CRC progression (6,39 Extraction, isolation and purification of histones. Cancer cell lines were harvested at 80% confluence through trypsination.…”
mentioning
confidence: 99%